2020
DOI: 10.1155/2020/1575730
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and Pharmacokinetics of a Commercial Saffron (Crocus sativus L.) Extract

Abstract: There are few studies about the pharmacokinetics of the low-molecular mass carotenoids crocetin or crocin isomers from saffron (Crocus sativus L.). None has been performed with a galenic preparation of a standardised saffron extract. The aim of the present research work was to study the effect of in vitro digestion process on the main bioactive components of saffron extract tablets and the corresponding pharmacokinetic parameters in humans. Pharmacokinetics were calculated collecting blood samples every 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 48 publications
(73 reference statements)
1
38
0
Order By: Relevance
“…Since saffron is widely cultivated and harvested in different parts of the world, planting methods can also vary based on climate, soil type, planting depth, and distance between corms. Recent studies [6][7][8] have shown that saffron has many pharmacological effects, such as anticonvulsant, antihypertensive, antitussive, antigenotoxic, anxiolytic, cytotoxic, antioxidant, antidepressant, anti-inflammatory, and Sci. Pharm.…”
Section: Introductionmentioning
confidence: 99%
“…Since saffron is widely cultivated and harvested in different parts of the world, planting methods can also vary based on climate, soil type, planting depth, and distance between corms. Recent studies [6][7][8] have shown that saffron has many pharmacological effects, such as anticonvulsant, antihypertensive, antitussive, antigenotoxic, anxiolytic, cytotoxic, antioxidant, antidepressant, anti-inflammatory, and Sci. Pharm.…”
Section: Introductionmentioning
confidence: 99%
“…Our results point to a role for CCT as a potential candidate to be included in pharmacological therapies aimed at reverting adipose tissue accumulation in diabesity. The therapeutic use of CCT is being investigated by various groups besides ourselves [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blood levels of selected terpenes after administration of a single dose and their effective concentrations which exert biological effects are presented in Table 2 [77][78][79][80][81][82][83][84][85][86]. In most cases a higher single dose is required to reach the effective terpene concentration in the serum; however, the half time of these compounds' elimination from the blood is rather long, and repeated doses or a daily diet containing these compounds may be sufficient to maintain a safe, but stable, effective concentration.…”
Section: Discussionmentioning
confidence: 99%